Cold arid Ladakh: A natural conservatory of folk apricot cultivars for horticultural use (Indian Journal of Arid Horticulture, 2018)
Traditional knowledge is the essence of social capital helps in the faster development of science in favour of human kind  through a holistic approach. Local culture, spirit, social and ethical norms possessed by local people has often been determining  factors for sustainable use, and conservation of biodiversity. In present paper, an effort has been made to converge the information  on traditional knowledge generated by the tribes of Ladakh about growing and conservation of folk apricot cultivars for  sustainable livelihood. To achieve this objective twenty-three major apricot growing villages of Ladakh from five different eco geographical regions i.e. Kargil, Khaltsi, Dha-Hanu, Leh and Nubra of Ladakh province have been considered. Study revealed  that there were forty-three major folk apricot cultivars are grown for commercial and house hold use. The peoples of Ladakh  gained location specific life-long experience and indigenous strategy for sustainable biodiversity use and management at  individual as well as community level. This has been built up through regular use and attentive observations related to fresh fruit,  drying and oil extraction purposes of fruits and kernels. The conserved materials of these folk cultivars are serving the country as  in-situ field gene banks. Which will be a boon to the development of apricot industry leads to the enhanced livelihood and  nutritional security.
Keywords: Traditional knowledge; apricot; Chulli; Ladakh; folk cultivars